2003
DOI: 10.1111/j.1572-0241.2003.08723.x
|View full text |Cite
|
Sign up to set email alerts
|

Intragastric Ph During Continuous Infusion With Pantoprazole in Patients With Bleeding Peptic Ulcer

Abstract: Compared with the infusion with 6 mg/h pantoprazole, the continuous infusion of 8 mg/h pantoprazole showed a lower interindividual variability of the intragastric pH and a greater percentage of time that pH was >/ or =6. Thus, with regard to safety and efficacy, an initial 80-mg bolus injection, followed by 8 mg/h continuous infusion, seems to be the adequate treatment in patients with a high risk of rebleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 35 publications
0
38
0
Order By: Relevance
“…Previous studies on intravenous infusion of pantoprazole have demonstrated its efficacy and safety in treating GERD [13], erosive esophagitis [14,15], Zollinger-Ellison syndrome [10], and acute gastrointestinal bleeding [11,12]. To our knowledge, our study is the first to show that intravenous infusion of pantoprazole, including infusion once a day or continuous infusion for 72 h, in treating severe esophagitis was efficient and safe.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Previous studies on intravenous infusion of pantoprazole have demonstrated its efficacy and safety in treating GERD [13], erosive esophagitis [14,15], Zollinger-Ellison syndrome [10], and acute gastrointestinal bleeding [11,12]. To our knowledge, our study is the first to show that intravenous infusion of pantoprazole, including infusion once a day or continuous infusion for 72 h, in treating severe esophagitis was efficient and safe.…”
Section: Discussionmentioning
confidence: 58%
“…The intravenous route provides an alternative for patients in whom oral administration is not possible. In addition, intravenous infusion produces a faster and steadier acid suppression than an does the oral regimen [10][11][12]. The safety of intravenous pantoprazole has been demonstrated in patients with GERD [13], with erosive esophagitis [14,15], with Zollinger-Ellison syndrome [10], or with bleeding ulcer [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The authors' conclusion was that these healing rates were similar to those obtained in other studies in which only oral pantoprazole was used. Other studies have demonstrated efficacy of initial therapy with IV pantoprazole at varying doses in a number of other clinical situations such as ZES [10], control of gastric pH in acute peptic ulcer bleeding [11], and stress ulcer prophylaxis in critically ill patients [12]. However, this is the only study on a PPI, to our knowledge, that documents a rigorous pharmacodynamic effect for IV PPI therapy in GERD patients when used as initial therapy.…”
Section: Discussionmentioning
confidence: 94%
“…As patients with comorbid illness had a higher risk of rebleeding, a higher dosage or prolonged duration of omeprazole infusion would be rationally indicated to prevent the risk of rebleeding [38]. An initial bolus injection of 80 mg pantoprazole, followed by a continuous infusion at 8 mg/h, has also been recommended for patients with a high risk of rebleeding [39].…”
Section: Complications Of Peptic Ulcer Diseasementioning
confidence: 99%